Sosialisasi Tata Cara Penggunaan Lalu Lintas dan Penyerahan Buku Edukasi Keselamatan Berkendara kepada Mahasiswa di Bangkinang - Yurisdian, Yurisdian; Adeswastoto, Hanantatur; Setiawan, Beny; Sari, Resy Kumala; Tanjung, Lailatul Syifa (Journal of Social and Community Service, 2022)
This community service activity aims to improve traffic safety literacy among university students through direct socialization and the donation of educational books to the campus library. The program was held at the Universitas Pahlawan Tuanku Tambusai Library in Bangkinang and featured a speaker from the Kampar District Transportation Department, Mr. Yurisdian. The materials presented covered traffic regulations, understanding road signs and markings, and ethical behavior in traffic. In addition to the presentation session, the activity included interactive discussions and a Q&A session. The handover of traffic literacy books marked a concrete effort to strengthen independent learning and long-term literacy within the academic environment. The results indicate high student enthusiasm and increased awareness of responsible driving practices. This activity is recommended for replication in other educational institutions to cultivate a sustainable culture of traffic discipline.